General dentists' readiness and barriers in intimate partner violence screening: a cross-sectional study in Jeddah City - Ehab N. Alshouibi (BMC, 2022)
Abstract Background Intimate partner violence (IPV) has varying prevalence rates and risk factors based on cultural, social, and economic backgrounds. However, it is common for IPV victims to be seen in dental settings on a regular basis. Identifying IPV victims in dental settings might help address this overlooked global dilemma. This study was conducted to evaluate general dentists' readiness and potential barriers to performing IPV screening in a dental setting. Methods A cross-sectional study was conducted using the Domestic Violence Healthcare Providers Survey (DVHPS). This validated and structured questionnaire was adopted, modified, and self-administered to evaluate general dentists' readiness and barriers to IPV screening. General dentists were recruited for the study population from 5 administrative territorial regions in Jeddah, Saudi Arabia. The questionnaire consists of 7 domains that assess general dentists' readiness and barriers to performing IPV screening for all dental patients. Results Out of the 273 dentists approached, a total of 200 participated in the study, with a total response rate of 73.3%. The percentages of female and male dentists were 54% and 46%, respectively. Almost 73% of the study population believed they could identify IPV in a dental setting. The multiple linear regression model indicated a substantial decrease in general dentists' readiness to perform IPV screening due to fear of offending patients, an increased number of patients treated per day, and professional role resistance. Conclusion The current study suggests the high readiness of general dentists to perform IPV screening for all patients. However, prominent barriers to implementing IPV screening for all patients include fear of offending patients, an increased number of patients treated per day, and professional role resistance. Postgraduate continuous education is encouraged to re-enforce the importance of IPV screening in dental settings.